Exploratory Mapping Research on Crowdfunding - Buana, Yud (Bina Nusantara University, 2018)
The research aimed to provide a systematic literature review of the available research evidence on crowdfunding. Tenets of keyword search and fit analysis were used to review the term of crowdfunding. It was used to reveal the ambiguity and variations in the literature, and to create a mapping for further research. This research explored and tried to form a corridor for crowdfunding according to business models, intermediary platforms, the planned strategy, the emergence of risks and decisions, regulation and governance, the value creation, and other thingssuch as humanitarian and other non-financial matter. The result shows that research in the business models of crowdfunding platform and successful strategy is the preferred topics. Then, it mostly comes from European and North America according to the number of publications.